ヒガシ ナンキョク,エンダービーランド,ナピーアコンプレックス ノ シゼン ザンリュウ ジキ - 船木, 實; フナキ, ミノル; Funaki, Minoru (1984)
P(論文) 東南極大陸ナピーアコンプレックスから採集された約38億年前の岩石試料について, 古地磁気学的研究を行った。得られた10個の試料のうち, 5個は交流消磁と熱消磁に対して安定であったが, 残りの5個の試料は不安定であった。安定な残留磁気を持つ試料は, 主に単磁区ないし擬単磁区構造を持つ磁鉄鉱である。変成年代などを考慮すると, ナピーアコンプレックスは25億年前の地球磁場を記憶し, 冷却速度が遅かったため, 地球磁場の変動も記憶している。最も信頼できる残留磁気の方向は, 480℃の熱消磁で得られ, その方向は, 伏角-82.9°, 偏角39.3°で, これから計算される古地磁気極は, 南緯75.0°, 東経14.5°である。 Paleomagnetic studies were performed with the oldest rocks reported (about 3800 m.y.), collected from the Napier Complex in East Antarctica. Five specimens have stable NRM against AF and thermal demagnetizations, but other five have unstable one. The main NRM carriers in the former specimens are pure magnetite of single-pseudosingle domain structure. The Napier Complex was remagnetized completely in the amphibolite facies metamorphism 2500 m.y. ago. Since the cooling rate of the Complex was very slow at that time, it recorded the changing geomagnetic field. The most reliable NRM direction obtained is -82.9°inclination and 39.3°declination by thermal demagnetization to 480℃, and the corresponding VGP position is calculated to be latitude 75.0°S and longitude 14.5°E. departmental bulletin paper